IV CULTURAL SHOW OF THE DENTISTRY COURSE: SOCIAL RELEVANCE AND DIVERSITY (CIPEEX, 2022)
THIS WORK PROPOSES TO PRESENT THE EXPERIENCE REPORT OF THE IV CULTURAL EXHIBITION OF THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS - UNIEVANGŠLICA, AND THIS CULTURAL SHOW, PROPOSES THE EXHIBITION AND / OR PUBLIC PRESENTATION OF WORKS. OBJECTIVE: TO INTEGRATE TEACHERS AND STUDENTS OF THE DENTISTRY COURSE THROUGH THE EXHIBITION AND PRESENTATION OF CULTURAL AND ARTISTIC ACTIVITIES. METHODS: THE DOCUMENTARY ANALYSIS WAS CARRIED OUT, HAVING AS INDICATORS THE NUMBER OF PAPERS PRESENTED, THE NUMBER OF PARTICIPANTS, AND THE EXCHANGE OF INFORMATION (FEEDBACK) BETWEEN TEACHERS AND STUDENTS. RESULTS: THERE WERE 214 STUDENTS AND INVITED GUESTS AND 23 TEACHERS. NINETEEN PAPERS WERE PRESENTED AS ACADEMIC MATERIAL, FIVE IN THE VIDEO FORMAT, TWO IN THE DRAMA FORMAT AND FOUR IN THE MUSICAL PRESENTATION FORMAT, TOTALING 30 WORKS PRESENTED. THROUGH CONVERSATIONS AMONG FACULTY MEMBERS, IT WAS NOTICED THAT MANY WERE EXTREMELY SATISFIED WITH THE EVENT, COMMITTING THEMSELVES TO ENCOURAGE ACADEMICS THROUGHOUT THE YEAR TO PRODUCE MATERIAL TO BE PRESENTED AT THE SHOW. THERE WAS INTEGRATION BETWEEN THE ACADEMICS OF DIFFERENT PERIODS AND BETWEEN THE PROFESSORS AND ACADEMICS. AN EVENT WITH MORE PARTICIPATION OF THE STUDENTS AND WITH GREATER NUMBER OF WORK / PRESENTATIONS IS EXPECTED FOR NEXT YEAR.&NBSP;PALAVRAS-CHAVE (OU KEYWORDS, OU PALABRAS CLAVE): COMMUNITY-INSTITUTION RELATIONS, DENTISTRY, CULTURE.